Groundwater potential zone mapping using geographic information systems and multi-influencing factors: A case study of the Kohat District, Khyber Pakhtunkhwa - Faheem, Haris; Khattak, Zeeshan; Islam, Fakhrul; Ali, Rashid; Khan, Rehan; Khan, Ilyas; Tag Eldin, Elsayed (Frontiers in Earth Science, 2023)
Groundwater is very important factor of life and without its potential identification, thus, it is very essential to identify ground water potential zones. For this purpose, the study area of district kohat was selected to identify the ground water potential zone by using multi influencing factors (MIF) approach. The Kohat area has semi-arid to sub humid subtropical climate, classified as a sub-tropical triple season semiarid sub-mountainous area. The geology, land use, soil, rainfall, lineament density and drainage density are the important influencing parameters of Groundwater Potential (GWP) identification. To study the relative effect of the influencing factors, which help to delineate the ground water potential zones. The GWP zones were reclassified into five zones i.e., very poor, poor, good, high, and very high. We determine that 37.72% area have high Ground water potential zone in study area which are mostly Near to North-West of the Study Area and 4.62% Area have very poor GWP zone Which are near to South-East of the study area. The water table of study are varies due to different parameters which are used to identify the ground water potential zones in the study. Our MIF results revealed that the large area of Kohat district has good water potential but due to Topographic Elevation changes, the ground water potential has been limited in the hilly areas. Additionally, our final results were compared with the water level data collected from different sources across the district Kohat.